Numerical Simulation of Alpine Flash Flood Flow and Sedimentation in Gullies With Large Gradient Variations - Ding, Yufei; Liu, Xingnian; Chen, Ridong (Frontiers in Environmental Science, 2022)
Alpine flash floods can form easily and quickly with large destructive power. Compared with floods occurring over plains, alpine flash floods are formed over scattered locations with complex terrain and data is often lacking regarding the land topography, flow and sedimentation, causing difficulties when developing mathematical models to predict flash floods. The existing flash flood models mainly focus on the influence of water flow, such as the sharp increase in flow discharge caused by convergence at steep slopes, disregarding the sediment load carried by the water flow. However, under the effect of high-intensity sediment transport, the sedimentation in gullies may lead to surges in water level, causing the phenomenon of "great disasters resulting from minor flooding". In this study, an efficient and accurate water-sediment coupling model was established with a Godunov-type finite volume method based 2D flow model, and a sediment module and OPENMP parallel computing module were added as well. Firstly, a common gully in mountainous area with large gradient variations was used as a generalized model to explore the impact of sedimentation on the flow field of the gully and compared with the physical model. Then, the alpine flash flood incident in Gengdi Village was simulated with the computer model. The calculation results show that the high-intensity sedimentation significantly increased the magnitude of alpine flash floods. Moreover, a sharp increase in water level was seen after the slope changed, accompanied with a reduction in flow rate. However, the sediment-carrying capacity of the water flow was much lower than the upstream sediment load; hence, sediment constantly moved up to the main gully, causing water level increase in a large area of the gully. These results are essentially identical to the actual impact of the Gengdi Village disaster. The research results verified that this mathematic model can efficiently, accurately and concisely predict the occurrence of flash floods in gullies with large gradient variations. The model also provides a flow and sediment modeling method that incorporates the effect of high-intensity sediment transport into the traditional flash flood flow model. This model can be a powerful tool for detecting flash floods.